Economic recovery in post-World War II West Germany and Ukraine today - Barry Eichengreen (EconPol Forum, 2023)
Historical experience suggests that network infrastructure can be reoriented and reconstructed relatively quickly in postwar Ukraine, with the central government playing a coordinating role. Repair of the housing stock may take longer, and chronic housing shortages leading to inadequate labor supply in some locations may handicap recovery and growth. A voucher program would enable households to choose where to live on the basis of economic opportunity and cost, and provide incentives for residential construction. Postwar Ukraine is likely to run very large current account deficits. Foreign direct investment and portfolio capital inflows will not provide the necessary finance. In addition, substantial foreign aid will be required. Steps should be taken now to coordinate the provision of aid through the creation of an independent administrator and multi-donor fund.
Keywords: 330